Tina's ParTy line: Polysubstance use patterns in sexual minority men living with HIV who use methamphetamine. (21st November 2021) - Davis Ewart, Leah; Johnson, Ariana; Bainter, Sierra; Brown, Eric C.; Grov, Christian; Harkness, Audrey; Roth, Alexis M.; Paul, Robert; Neilands, Torsten B.; Dilworth, Samantha E.; Carrico, Adam W.
Abstract: Introduction: This cross‐sectional study examined the associations of demographic, structural and psychological factors with distinct typologies of polysubstance use in sexual minority men (SMM) living with HIV who use methamphetamine. Methods: In total, 161 SMM living with HIV who reported methamphetamine use in the past 3 months were recruited in San Francisco from 2013 to 2017 for a randomised controlled trial. A latent class analysis was conducted by leveraging baseline measures of self‐reported use of 15 substances in the past 3 months as well as validated screening measures of hazardous alcohol and cannabis use. Correlates of latent class membership were examined using a three‐step categorical latent variable logistic regression. Results: Four typologies of substance use were identified: (i) methamphetamine use only (43%); (ii) methamphetamine and crack‐cocaine use (22%); (iii) party and play use—methamphetamine, gamma‐hydroxybutyrate and amyl nitrites (i.e. poppers) with erectile dysfunction drugs (31%); and (iv) high polysubstance use (4%). SMM of colour and those with a history of incarceration were more commonly classified as engaging in methamphetamine and crack‐cocaine use compared to party and play use. Men with higher sexual compulsivity scores were more commonly classified as engaging in party and play use and polysubstance use. Discussion and Conclusions: There is substantial heterogeneity in polysubstance use patterns among SMM living with HIV who use methamphetamine. This will inform the development of tailored substance use interventions addressing the unique needs of SMM of colour and targeting sexual compulsivity as a prominent comorbidity for some men.